The effects of acceptance and commitment therapy (ACT) on psychological and physical outcomes among cancer patients and survivors: an umbrella review - Sauer, Christina; Haussmann, Alexander; Weißflog, Gregor Joachim (Journal of Contextual Behavioral Science, 2024)
Background - Acceptance and Commitment Therapy (ACT) is a promising approach in psycho-oncology that has led to an increasing number of studies and reviews. This systematic umbrella review provides a comprehensive overview of the results of existing systematic reviews and meta-analyses to investigate the trans-symptomatic (i.e., psychological and physical symptoms) efficacy of ACT in the context of cancer. The study addresses both physical and psychological outcomes, aiming to identify existing research gaps and delineate potential focal points for future studies exploring the application of ACT in psycho-oncological settings. - Methods - A systematic literature search was conducted in Pubmed, Ebsco Host Academic Search Complete (incl. APA PsycInfo), Web of Science, Cochrane Library, website of the Association of Contextual Behavioral Science (ACBS), and Prospero. To be included, studies had to meet the following criteria: 1) be a systematic review and/or meta-analysis focusing on ACT and its impact on psychological and physical outcomes in cancer patients or survivors; 2) include only patients with oncological conditions; 3) be published in English. The quality of the reviews and meta-analyses was assessed using the AMSTAR 2 criteria. - Results - We included eight systematic reviews and meta-analyses in our synthesis. Results of the reviews and meta-analyses indicate that ACT interventions increase the health-related quality of life (HRQoL) and psychological flexibility, and reduce depression, anxiety, and psychological distress in cancer patients and survivors. The best evidence exists regarding psychological distress and HRQoL. The efficacy of these interventions concerning other psychological outcome measures (e.g., fear of progression/recurrence, hope) and biological parameters has not yet been well investigated. Moderator analyses revealed larger effects for younger patients, individuals from Eastern countries (Iran, China), and after longer intervention durations. Results suggest potential differential effects based on the cancer stage. According to the AMSTAR 2 criteria, the quality of the included reviews was low or critically low. - Conclusion - Recent meta-analyses and reviews suggests that ACT interventions are an effective and evidence-based treatment for increasing HRQoL and reducing psychological distress in patients with cancer. However, the results should be interpreted with caution, as the quality of the included reviews was generally low. Our synthesis highlights the need for more high-quality randomized controlled trials, reviews, meta-analyses, and mediator analyses in this research area.
Online veröffentlicht am 2. August 2024, Artikelversion: 4. August 2024
Gesehen am 08.04.2025